Aplicativo offline para evidencias de traspaso de materiales educativos en zonas rurales sin conectividad a internet en Maynas 2023 - Gonzales Sinuiri, Josué Luis (2024)
The thesis research carried out sought to strengthen the process of obtaining evidence in areas with a lack of internet service, in the annual process of distribution of educational teaching-learning materials in educational institutions (IIEE) throughout the scope of scope. of the Maynas Local Educational Management Unit (UGEL Maynas). The general objective of the research was to determine if an offline application can improve the evidence of transfer of educational materials in rural areas with a lack of internet connectivity in the province of Maynas in the year 2023. The methodology of The research was observational, non-experimental, descriptive, applied and transversal. Our population was made up of 65 IIEE that were selected among the 1374 educational institutions distributed in 8 material delivery routes at the UGEL Maynas in the Loreto Region during the year 2023. The results obtained support the proposed hypothesis, allowing room for this type process and contexts similar to the use of offline applications to improve the monitoring and control of the distribution of educational materials in areas without internet service.